Impaired Mitochondrial Energetics Characterize Poor Early Recovery of Muscle Mass Following Hind Limb Unloading in Old Mice. (19th March 2018) - Zhang, Xiaolei; Trevino, Michelle B; Wang, Miao; Gardell, Stephen J; Ayala, Julio E; Han, Xianlin; Kelly, Daniel P; Goodpaster, Bret H; Vega, Rick B; Coen, Paul M
Abstract: The progression of age-related sarcopenia can be accelerated by impaired recovery of muscle mass following periods of disuse due to illness or immobilization. However, the mechanisms underlying poor recovery of aged muscle following disuse remain to be delineated. Recent evidence suggests that mitochondrial energetics play an important role in regulation of muscle mass. Here, we report that 22- to 24-month-old mice with low muscle mass and low glucose clearance rate also display poor early recovery of muscle mass following 10 days of hind limb unloading. We used unbiased and targeted approaches to identify changes in energy metabolism gene expression, metabolite pools and mitochondrial phenotype, and show for the first time that persistent mitochondrial dysfunction, dysregulated fatty acid β-oxidation, and elevated H2 O2 emission occur concomitantly with poor early recovery of muscle mass following a period of disuse in old mice. Importantly, this is linked to more severe whole-body insulin resistance, as determined by insulin tolerance test. The findings suggest that muscle fuel metabolism and mitochondrial energetics could be a focus for mining therapeutic targets to improve recovery of muscle mass following periods of disuse in older animals.